Calculation of Tabarru Funds Using Makeham's Mortalita Law and Gompertz's Mortalita Law Using the Cost Of Insurance Method - Tauki Rohman Muzaki; Emy Siswanah; Seftina Diyah Miasary (Journal of Natural Sciences and Mathematics Research, 2020)
Tabarru funds have the meaning of a collection of funds given by insurance participants as a virtue fund with sincere intentions for the purpose of helping one participant with another if one of them gets a disaster. The tabarru fund management mechanism in Indonesia uses two types of operational systems, namely the product saving system (savings) and the non-saving product system. Management with a saving product system uses a savings mechanism with 5% for management funds. Meanwhile, in the non-saving product system with a no-savings mechanism, the amount and its management are not yet known, which will cause confusion for the community in the calculation. The cost of insurance method is one method that can be used to calculate tabarru funds. This method calculates tabarru funds by multiplying the percentage of tabarru funds by the cost of coverage. The percentage of tabarru funds is searched through the mortality table, management fee, and investment level. From the management fee of 25% and the investment rate of 5%, the percentage of tabarru funds using Makeham's mortality law is  for men and for men. Meanwhile, Gompertz's law of mortality obtained  for men and for women . ©2020 JNSMR UIN Walisongo. All rights reserved.